Driving Market Confidence: The Role of ESG Reporting in Green Finance Transparency - Nazaf Quaser (Advanced Business Journal, 2026)
The escalating prioritization of sustainability within global capital markets has positioned Environmental, Social, and Governance (ESG) reporting as a cornerstone for fostering transparency and accountability. As investors and regulators increasingly look beyond traditional financial metrics to gauge long-term value and corporate responsibility, ESG disclosures have become indispensable for evaluating non-financial risks. This study examines the instrumental role of ESG reporting in enhancing market clarity and its broader implications for sustainable finance practices. Adopting a qualitative analytical lens, the research conducts a systematic review of peer-reviewed literature, international disclosure standards, and evolving regulatory frameworks, supplemented by secondary data from institutional sustainability reports. The findings demonstrate that high-quality ESG reporting serves to bridge the gap of information asymmetry, thereby bolstering investor confidence through more precise performance assessments. Furthermore, the evidence suggests that consistent and standardized disclosures lead to more efficient capital allocation and a reduction in perceived corporate risk. However, the study also identifies that the current fragmentation of reporting standards remains a formidable barrier to systemic effectiveness. The research concludes that while ESG reporting is a vital catalyst for advancing sustainable finance, its ultimate success depends on the harmonization of global standards, robust governance, and the implementation of credible verification processes.